2015
DOI: 10.1111/fcp.12126
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib–ibuprofen drug interaction affects the pharmacokinetics and tissue distribution of sunitinib to brain, liver, and kidney in male and female mice differently

Abstract: Tyrosine kinase inhibitor sunitinib (used in GIST, advanced RCC, and pancreatic neuroendocrine tumors) undergoes CYP3A4 metabolism and is an ABCB1B and ABCG2 efflux transporters substrate. We assessed the pharmacokinetic interaction with ibuprofen (an NSAID used by patients with cancer) in Balb/c male and female mice. Mice (study group) were coadministered (30 min apart) 30 mg/kg of ibuprofen and 60 mg/kg of sunitinib PO and compared with the control groups, which received sunitinib alone (60 mg/kg, PO). Sunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…At therapeutic dosages, imatinib, lapatinib, and sunitinib typically reach plasma concentrations in the range of 5, 4, and 0.3 μM, respectively (Huynh et al, 2017). As shown by data in mice, the concentrations in liver may be higher than in plasma by a factor of 2 for imatinib (Tan et al, 2011) and by a factor of at least 10 for lapatinib (Spector et al, 2015) and sunitinib (Lau et al, 2015), suggesting that toxic liver concentrations can be reached in certain patients. The data of the current study and clinical experience suggest that exposure is an important risk factor for liver toxicity associated with TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…At therapeutic dosages, imatinib, lapatinib, and sunitinib typically reach plasma concentrations in the range of 5, 4, and 0.3 μM, respectively (Huynh et al, 2017). As shown by data in mice, the concentrations in liver may be higher than in plasma by a factor of 2 for imatinib (Tan et al, 2011) and by a factor of at least 10 for lapatinib (Spector et al, 2015) and sunitinib (Lau et al, 2015), suggesting that toxic liver concentrations can be reached in certain patients. The data of the current study and clinical experience suggest that exposure is an important risk factor for liver toxicity associated with TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of apoptosis indicated by caspase 3/7 activity increased at 20 µM sunitinib, while PARP degradation occurred at 10 µM sunitinib. Although plasma concentrations of sunitinib are 0.1–0.3 µM, concentrations in the liver might be 10-fold higher [68]. This suggests that dose and concentration may play a role in the hepatotoxicity of sunitinib.…”
Section: Downstream Toxicity Mechanisms Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…The effect of sex differences on the pharmacokinetics and tissue distribution of TK inhibitor sunitinib was evaluated in a preclinical mouse model (Lau et al, 2015; Liew et al, 2017). In both studies, statistically significant differences between sunitinib exposure in male and female mice were found in plasma, liver, brain, and kidney tissue.…”
Section: Translational Approach Of Covariate Sex On Sunitinibmentioning
confidence: 99%
“…Sex-based DDI outcome differences were observed upon coadministration of sunitinib with selected NSAIDs, used to reduce cancer pain or side effects related to the treatment (Ripamonti et al, 2014; Hammer et al, 2016; Mercadante and Portenoy, 2016). In preclinical studies, dramatic sunitinib plasma and tissue exposure effects were observed after coadministration with ibuprofen (Lau et al, 2015), paracetamol (Liew et al, 2017) or diclofenac (Chew et al, 2017). These effects included changes of sunitinib plasma exposure and most importantly, changes in brain, liver, and kidney sunitinib penetration that were different in male and female mice showing sex-different plasma-tissue DDI outcomes ( Table 1 ): diclofenac and paracetamol decreased plasma exposure in male mice which compares with a general reduction of sunitinib exposure in tissues of interest.…”
Section: Translational Approach Of Covariate Sex On Sunitinibmentioning
confidence: 99%